Asymmetric response of unemployment rate to export shock in Indonesia: Does educational attainment matter? - Sielvia Sari; Mohamad Khusaini; Makoto Kakinaka (Publisher of Widyagama University of Malang (UWG Press), 2022)
Indonesia has long struggled with a high rate of unemployment. Export, one of the aggregate demand’s components, typically affects the unemployment rate as argued by Keynes. Therefore, this study attempts to evaluate the asymmetric response of unemployment rate to export shock in Indonesia. Employing a Local Projection method, the analysis incorporates three important features: the asymmetric effects of export shock (positive or negative), business cycle (boom or slump), and educational attainment of workers (highly-educated or less-educated). Dataset consisted of province-level annual panel data of 18 provinces in Indonesia where the main ports for export activity are located, spanning from the years of 1990 to 2019. This study finds significant differences in the unemployment rate dynamics between less-educated and highly-educated workers. A positive export shock during the boom reduced the unemployment rate for less-educated workers, and the effect is more persistent. In contrast, highly-educated unemployment rate decreased when a positive export shock occurs during the slump period, and the effect was rather in the short run. These results suggest some policy implications such as strengthening the domestic market, relaxing export regulation on labor-intensive industries, and diversifying export products to enlarge job opportunities for highly-educated workers with varied qualifications.JEL Classification E24; I25; O24